Does COVID-19 stop night market's traders from losing their income? / Mas Affandy Mashuri - Mashuri, Mas Affandy (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Night markets, also known as night bazaars, are nighttime street markets that are devoted to more leisurely strolling, browsing, and dining than daytime markets. Usually, they are open-air economies. Locals refer to night markets as Pasar Malam, which simply translates to "night market," with "pasar" referring to "bazaar" in Persian or "market" in Malay, and "malam" referring to "night." A pasar malam is a night-time street market found in Malaysia, Singapore, and Indonesia, typically in residential areas. Since the vendors travel around various neighborhoods on different days of the week, a night market usually only happens once or twice a week. Most people like going to night markets because of the ease, lower prices, the opportunity to browse for fun, the temptation of local food that is not available in supermarkets, and the opportunity to walk. Currently, members of the public are concerned about the National Security Council's decision to allow Pasar Malam to work from 4pm to 10pm during the Movement Control Order 2.0, after Malaysia reported more than 5,000 new Covid19 cases (MCO). Many worried that reopening Pasar Malam would be a mistake in the fight against Covid-19, as authorities try to strike a balance between lives and well-being. Therefore, this study aims to recognize and address the preventative factors that would be used by authorities and government to prevent the pandemic Covid-19 from spreading while also boosting the economy and assisting Pasar Malam's traders in weathering difficult times. The study entails content analysis, which helps the researcher to explore further into the conceptual and theoretical questions raised by the data obtained from previous studies and other secondary sources. The overall results show that the prevention methods that can be practiced throughout the night market in Malaysia, namely, cashless payment mechanism and the use of thermal imaging scanners. The study concludes that the prevention methods can breaks the virus from spread as well as helps our night market owners especially those from the B40 income group that make up most of our traders.